1990
DOI: 10.1159/000171278
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Comparison of 24-Hour Intragastric pH Recording Using Glass and Antimony Electrodes in Man

Abstract: Based upon the results of in vitro studies, antimony electrodes are generally considered to have inferior electrochemical properties when compared with glass electrodes. Since a direct comparison in man is lacking, a 24-hour ambulatory intragastric pH recording was performed in 10 healthy male subjects simultaneously using glass and antimony electrodes. In the first set of experiments (when both electrodes were calibrated in buffers of pH 7 and 1 at 37 °C: beaker calibration) significantly lower pH recordings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…We do not have a clear explanation for this but it could be related to antimony pH electrode properties. It is well known that glass electrodes have superior electrochemical properties to antimony electrodes 33 but it has been suggested that comparable recordings of 24‐h intragastric pH in humans can be obtained with the latter 34 . Another explanation is that PPI including omeprazole and lansoprazole inhibit gastric acid secretion by selectively and non‐competitively inactivating the H + K + adenosine triphosphatase (ATPase) molecules of the parietal cell, but possibly only those that are actively secreting acid.…”
Section: Discussionmentioning
confidence: 99%
“…We do not have a clear explanation for this but it could be related to antimony pH electrode properties. It is well known that glass electrodes have superior electrochemical properties to antimony electrodes 33 but it has been suggested that comparable recordings of 24‐h intragastric pH in humans can be obtained with the latter 34 . Another explanation is that PPI including omeprazole and lansoprazole inhibit gastric acid secretion by selectively and non‐competitively inactivating the H + K + adenosine triphosphatase (ATPase) molecules of the parietal cell, but possibly only those that are actively secreting acid.…”
Section: Discussionmentioning
confidence: 99%
“…However, as with ammonium, general and specific aspects must be taken into account. The measuring mode (perendoscopic or in gastric aspirates), the type of sensitive electrode, the temperature, the heat produced by stirrer, the noise peaks, the position of the probe, the viscosity, etc., may significantly influence the measurement [33,34,35,36]. These conditions may only partially be controlled by corrective tricks (Fourier’s filtration, modified Nernst equation, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…These conditions may only partially be controlled by corrective tricks (Fourier’s filtration, modified Nernst equation, etc.) [33,34,35]; some of their effects still persist and maybe account for the discrepancies reported in the literature about gastric pH [20,21,22,23,24]. …”
Section: Discussionmentioning
confidence: 99%
“…Perhaps one of the most sensitive factors influencing study results is the pH-sensitive electrode. 12 Because there have been several reports that the electrochemical properties of antimony electrodes are inferior to those of glass e l e c t r~d e s ,~~~~~"~ and in view of glass electrodes being most commonly used for intragastric pH measurements currently, the use of glass electrodes may be recommended as a standard of intragastric pH recording in clinical trials. Standardization of the timing of food and liquid intake is of paramount importance during a clinical study.…”
Section: Discussionmentioning
confidence: 99%